me ajudem pfvv, eu preciso disso agora pfffffffvv
Anexos:
![](https://pt-static.z-dn.net/files/db8/092b8e72cf86083a46ebff610f4529ff.jpg)
Soluções para a tarefa
Respondido por
1
Resposta:
f(x)=2x-1 (x,y)
f(-2)= 2*(-2)-1=-4-1=-5 (-2 ,-5)
f(-1)=2*(-1)-1=-2-1=-3 (-1 , -3)
f(0)=2*0-1=0-1=-1 (0 , -1)
f(1)=2*1-1=2-1=1 (1 , 1)
Explicação passo-a-passo:
analuiza91218:
muito obrigado
Perguntas interessantes
Ed. Física,
8 meses atrás
Matemática,
8 meses atrás
Filosofia,
9 meses atrás
Biologia,
9 meses atrás
ENEM,
1 ano atrás
ENEM,
1 ano atrás
ENEM,
1 ano atrás